Identification of sensitive periods of weight status transition over the lifespan in Chinese population - Chaonan Gao; Xin Meng; Wei Liu; Qianjin Qi; Yinkun Yan (BMC Medicine)
Abstract Background The prevalence of high body mass index (BMI) is increasing in both children and adults worldwide. However, it is unclear whether vulnerabilities to maintenance and transition of weight status vary throughout the lifespan. Objective We aimed to characterize dynamic transitions of weight statuses across different life stages and to identify the sensitive periods for maintenance, onset, and resolution of obesity. Methods This longitudinal study included a total of 23,179 participants aged 6–80 years with 95,994 BMI measurements from the China Health and Nutrition Survey 1989–2015. To examine the heterogeneity in transitions of weight statuses across different life stages, we divided participants into 8 sub-cohorts based on baseline ages by 10-year intervals, i.e., 6–10 years, 11–20 years, 21–30 years, 31–40 years, 41–50 years, 51–60 years, 61–70 years, and 71–80 years. We estimated the probabilities of transitioning between weight statuses at a given follow-up year by baseline age using generalized linear mixed-effects models. Results The predicted prevalence of obesity decreased from 6 years, bottomed at around 20 years, increased thereafter, peaked at around 55 years, and then decreased gradually. In general, participants with underweight had lower probabilities of maintaining the same status compared to those with normal weight, overweight, or obesity for all age groups. For 10-year follow-up, individuals aged 21–30 years had the highest probabilities of transitioning from normal weight to obesity and transitioning from overweight to obesity compared to those in other age groups. Individuals aged 6–20 years had the highest probabilities of transitioning from obesity to normal weight and transitioning from overweight to normal weight. Individuals in all adult age groups had higher probabilities of maintaining obesity status than children and adolescents. Conclusions Young adulthood is the most sensitive period for obesity onset, whereas childhood and adolescence are the most sensitive periods for obesity resolution. The findings suggest the heterogeneity of susceptibilities to weight status transitions across different life stages and highlight the importance of the development of age-appropriate approaches for the prevention and intervention of obesity.